Ineffective and prolonged apical contraction is associated with chest pain and ischaemia in apical hypertrophic cardiomyopathy. (15th January 2018) - Stephenson, Edward; Monney, Pierre; Pugliese, Francesca; Malcolmson, James; Petersen, Steffen E.; Knight, Charles; Mills, Peter; Wragg, Andrew; O'Mahony, Constantinos; Sekhri, Neha; Mohiddin, Saidi A.
Abstract: Objectives: To investigate the hypothesis that persistence of apical contraction into diastole is linked to reduced myocardial perfusion and chest pain. Background: Apical hypertrophic cardiomyopathy (HCM) is defined by left ventricular (LV) hypertrophy predominantly of the apex. Hyperdynamic contractility resulting in obliteration of the apical cavity is often present. Apical HCM can lead to drug-refractory chest pain. Methods: We retrospectively studied 126 subjects; 76 with apical HCM and 50 controls (31 with asymmetrical septal hypertrophy (ASH) and 19 with non-cardiac chest pain and culprit free angiograms and structurally normal hearts). Perfusion cardiac magnetic resonance imaging (CMR) scans were assessed for myocardial perfusion reserve index (MPRi), late gadolinium enhancement (LGE), LV volumes (muscle and cavity) and regional contractile persistence (apex, mid and basal LV). Results: In apical HCM, apical MPRi was lower than in normal and ASH controls (p < 0.05). In apical HCM, duration of contractile persistence was associated with lower MPRi (p < 0.01) and chest pain (p < 0.05). In multivariate regression, contractile persistence was independently associated with chest pain (p < 0.01) and reduced MPRi (p < 0.001). Conclusion: In apical HCM, regional contractile persistence is associated with impaired myocardial perfusion and chest pain. As apical myocardium makes limited contributions to stroke volume, apical contractility is also largely ineffective. Interventions to reduce apical contraction and/or muscle mass are potential therapies for improving symptoms without reducing cardiac output. Graphical abstract: Image 1